The Cineautistic Detective: Steve Erickson’s “Zeroville” and the New Hollywood Novel - Antonio Di Vilio (Iperstoria, 2021)
This article proposes a reading of Steve Erickson’s Zeroville (2007) as a post-noir mystery novel in which the ‘cineautistic’ detective Vikar, haunted by the ghosts of his Hollywood myths, brings out the cultural meaning behind the fatal date 1969. Going beyond the tropes of the Hollywood Novel, as a solitary detective who tries to relate to the fragmented space that surrounds him, Vikar will shed some light not so much on the industry’s dehumanizing capabilities—which the classic Hollywood novels aimed to uncover—but on the force of the medium and its conventions. Vikar’s great skills as a film editor will piece together the clues in order to solve a metaphysical cinematic mystery and to confront the cultural transition represented by the New Hollywood and television. As Zeroville’s storyworld proves to be rooted in film experience, this essay also aims to detect the cinematic references and to analyze their meaning in relation to the novel’s discourse on medium.